Enhancing Students’ Creative Thinking Skills in Renewable Energy through POPBL-FC with Rasch Model Analysis - Elvira Clarita Melur; Andhy Setiawan; Achmad Samsudin (PAEDAGOGIA, 2026)
Creative thinking skills are essential competencies in 21st-century education, particularly in addressing global challenges related to sustainable energy. However, students’ creative thinking skills in physics learning are still relatively low and require improvement through innovative instructional approaches. This study aims to examine the effectiveness of the Project-Oriented Problem-Based Learning–Flipped Classroom (POPBL-FC) model in enhancing students’ creative thinking skills in renewable energy topics using Rasch analysis. A quantitative approach was employed, using a quasi-experimental non-equivalent control-group design involving two Grade X classes at a senior high school in Alor Regency, Indonesia. The sample consisted of 33 students in the experimental class and 31 students in the control class, selected through cluster random sampling. The results of the Rasch analysis revealed a significant improvement in students’ creative thinking skills in the POPBL-FC group, as indicated by an increase of +2.39 logits, with all students demonstrating positive ability shifts. In contrast, the control group showed relatively lower improvement, with several students exhibiting no significant progress. These findings indicate that the POPBL-FC model is effective in fostering students’ creative thinking skills in physics learning, particularly in renewable energy topics. Furthermore, the application of Rasch analysis provides a robust and reliable measurement framework for capturing changes in students’ abilities more precisely, thereby contributing to more accurate evaluation in educational research contexts.